Gender Differences in Risk-Taking and Sensation-Seeking Behavior: Empirical Evidence from “ExtremeSports” - Bernd Frick (De Economist, 2020)
Do men and women differ with respect to sensation-seeking behavior, an extreme form of risk preferences? In this paper, I use data from two different high-risk sports—cliff diving and free diving—to test for possible differences between the genders. My findings suggest that, first, women are under-represented in both sports, but that, second, for those who self-select into these occupations, no differences with respect to sensation-seeking behavior can be found between men and women.
Keywords: J16; J24; J29; J49; Z20; 330; Risk preferences; Sensation-seeking; Gender differences; Self-selection; Extreme sports